Electric field numerical analysis and structure optimization of grounding switch in GIS based on finite element analysis. Issue 1 (1st October 2022) - Feng, Miao; Wang, Ming; Zhang, Qingxian; Tan, Heyi; Li, Xiaozhe; Zeng, Dehua; Yang, Tao; Zhang, Mao
Abstract: The grounding switch is an important component to ensure safety on its GIS and maintenance personal. In this paper, the COMSOL Multiphysics software is used to carry out electrostatic field analysis on grounding switch in GIS by the finite element method. This study also did a lot of research including drawing 3D models of key parts, gridding division and post-processing the data of electric field. The field intensity distribution diagrams and the maximum value of field intensity concentration area of key insulation position at 1100kV and 500kV are obtained. The electric field intensity distribution of GIS near the static contactor of the grounding switch is discussed, and the design of appropriately increasing the radius of the conductor in the part the great abrasion is proposed, and it provides a theoretical basis for the electric field distribution of electrical equipment.